Reconstruction of the Police Intelligence Legal System to Address the Failure of Decision-Making in Detecting Transnational Crimes in a Just and Legally Certain Way - Giovanni Ruben Siregar; Yopik Gani; Kif Aminanto (Journal Customary Law, 2026)
This study seeks to examine weaknesses in the police intelligence legal framework in detecting and making decisions related to transnational crimes, as well as to reconstruct the system by introducing predictive policing and an integrated criminal intelligence approach that ensures fairness and legal certainty. The research employs a normative juridical method with statutory and conceptual approaches, analyzing the 1945 Constitution of the Republic of Indonesia, Law Number 2 of 2002 on the Indonesian National Police, Law Number 17 of 2011 on State Intelligence, and other relevant regulations concerning transnational crime and police intelligence. The findings show that the shortcomings of police intelligence in addressing transnational crime stem from regulatory inconsistencies, weak integration of intelligence data, limited inter-agency coordination, unclear decision-making procedures, and insufficient oversight and human rights safeguards. These conditions indicate that conventional law enforcement methods are increasingly inadequate in responding to transnational crimes that are cross-border, organized, and technologically advanced. This research proposes a reconstruction of the police intelligence legal system through regulatory reform, the development of an integrated criminal intelligence system, the strengthening of predictive policing based on artificial intelligence and big data analytics, the establishment of an independent oversight mechanism, and the strengthening of international cooperation to create a modern, preventative, predictive, accountable, and equitable police intelligence system for combating transnational crime.